Gestão e produção cultural de mulheres nos festivais de inverno de Minas Gerais: resistência e enfrentamento político na cultura mineira - Gabriella de Oliveira Seabra (2024)
This research seeks to discuss how the production and management of women in the Minas Gerais Winter Festivals: Forum das Artes and UFMG enables the inclusion and debate of gender issues in the public sphere. To this end, we will look at the editions that took place between 2017 and 2019 of two Winter Festivals in Minas Gerais (Ouro Preto, Mariana and João Monlevade and the Federal University of Minas Gerais in Belo Horizonte). From this perspective, this research intends to survey and analyze the presence of women artists within the scenario of the two events, both the production and management of shows and groups that presented the festivals during this period, as well as the team responsible for carrying out these events. To this end, webs of dialogue will be created with diversity policies, feminism, gender debate and work dynamics in management and production professions to investigate the directions of this work relationship that permeates gender, public policies and a close look at an area on the rise in the art market.